"Blackening the ways": the Mapinduzi Collective and the promotion of black intellectuality (PerCursos, 2024)
In the face of the historic struggles of black people in Brazil, affirmative policies and discussions about the urgency of an anti-racist society/education are expanding. This movement encounters systematic barriers arising from whiteness and racism and, in universities, specifically, they negatively impact the training of teachers and education professionals. In response to this logic, university students from the Pedagogy course at the State University of Ceará (UECE) took action in 2021, founding the “Mapinduzi Collective”: a reading group of black intellectuals, a place of affection, dialogue and resistance. Thus, this article's general objective is to reflect on the construction of places to promote black intellectuality based on the experience at the Mapinduzi Collective/UECE. This is a qualitative research, a report of this experience of student "aquilombamento" that is strengthened by the intersectional perspective to discuss teacher education. The main discoveries confirm the absence of studies of black intellectuals during Pedagogy training, which report an institutionally whitened curriculum. Also noteworthy is the autonomy, boldness, power and avant-garde experience written by the Mapinduzi Collective, by creating and opening a permanent space to present, discuss and construct black thought within the University, welcoming students, the majority of whom are black, eager to meet and be black intellectuals.
Keywords: black intellectuals; anti-racist education; UECE pedagogy; Mapinduzi Collective